Pembelajaran Proyek Dalam Mengembangkan Literasi Numerasi Dan Literasi Sains Pada Anak - Yetty Isna Wahyuseptiana; Oka Irmade (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study aims to determine the application of project learning in developing numeracy literacy skills and scientific literacy in children. Numerical literacy ability is the ability to solve problems that occur in the surrounding environment by applying knowledge related to numbers and symbols in mathematics. Scientific literacy is one of the abilities that children need to have in the 21st century today. This research uses a qualitative case study approach. Data collection methods used include observation methods, interview methods, and documentation methods. The data in this study were analyzed by data reduction, data presentation, and drawing conclusions. Conducting research at Aisyiyah Kindergarten Cekel Karangturi, Karanganyar. In this study, it is explained about the ability of numeracy literacy and scientific literacy ability in early childhood at this time. Factors in influencing numeracy literacy skills and scientific literacy skills in early childhood and explaining the implementation of a learning project that aims to develop numeracy literacy skills and scientific literacy skills in early childhood. The conclusions in this study explain that numeracy literacy skills and scientific literacy skills in early childhood can be developed based on children's needs. The role of the teacher also contributes to assisting the implementation of learning using a project approach.